Targeting the Xylella fastidiosa spittlebug vector Neophilaenus campestris in the olive cover crops with the entomopathogenic fungus Metarhizium brunneum - Juan Carlos Conde-Bravo; María Fernández-Bravo; Inmaculada Garrido-Jurado; Meelad Yousef-Yousef; Enrique Quesada-Moraga (Frontiers in Insect Science)
IntroductionNeophilaenus campestris (Fallén) (Hemiptera: Aphrophoridae) is among the most abundant, highly dispersible, and widely distributed Xylella fastidiosa Wells (Xanthomonadales: Xanthomonadaceae) vectors to olive tree in Europe, with emphasis in Andalucía. The development of efficient and environmentally friendly vector management strategies is greatly needed. Entomopathogenic ascomycetes are among the few alternatives for the microbial control of pierce-sucking spittlebugs due to their unique contact mode and ability to endophytically colonize crops. These characteristics allow for several strategic uses aimed at reducing vector populations and/or their disease transmission potential. This study included a two-year field experiment to evaluate the Metarhizium brunneum Petch. (Ascomycota: Hypocreales) strain EAMa 01/58-Su sprayed onto N. campestris population naturally present in the olive grove cover in Cordoba (Spain).MethodsExperiments were conducted in early spring, and efficacy was evaluated using the Henderson-Tilton formula, as well as by analyzing changes in the relative population density of both nymphs and adults.Results and discussionThe fungus was detected in the soil and endophytically in the natural cover throughout the 8 days monitoring period, in which the fungal treatment significantly reduced both the nymph and the adult populations. Notably, the efficacy of the fungal treatment was 100.0% and 85.0% for foams and adults in 2023, and 62.5% and 72.0% for foams and adults in 2024, respectively. Results indicate a significant reduction in the population density of both vector developmental stages, highlighting the potential of this fungal strain for managing X. fastidiosa vectors in olive cover crops.